Exploring Ideational Meaning In Taylor Swift’s All Too Well - Putri Khayla Risqi Firdiani Fasa; Maulida Nazila Zahra; Nagita Slavina; Titania Sabrina (Jurnal Pendidikan dan Inovasi Pembelajaran, 2026)
This study aims to analyze the ideational meaning in Taylor Swift's song All Too Well using the Systemic Functional Linguistics (SFL) theoretical framework, specifically the ideational metafunction through the transitivity system. The focus of this study is to identify the types of processes used in the song lyrics, especially mental and relational processes, in expressing the emotional experiences and personal memories of the characters in the song. This study uses a qualitative descriptive method with text analysis techniques. The data, in the form of the lyrics of All Too Well, are analyzed by identifying clauses and grouping them based on the types of transitivity processes according to Halliday's theory. The results show that the song lyrics are dominated by mental and relational processes. Mental processes describe the character's feelings, memories, and self-reflection, while relational processes show identity, relationships, and emotional conditions. Material processes appear in limited numbers and function as supporting backgrounds. These findings indicate that the ideational meaning of the song focuses on the character's inner experiences and emotional relationships.